Cumplimiento De Obligaciones Patronales De La Dirección Distrital 12d01 – Baba, Babahoyo, Montalvo – Salud - Olivo Gamarra, Melida Dalila (2019)
The District Directorate 12D01 - Baba, Babahoyo, Montalvo - Health, is a State entity, dedicated to the management of health services of all the cantons that it covers, to fulfill this mission it has employees that contribute with their work to be able to achieve the assignment; However, this institution is in breach of employer obligations with the Ecuadorian Institute of Social Security - IESS, for the payment of personal and employer contributions; that the entity as such must perform for each of its employees. By not complying with what is stipulated in the Social Security Law, ie the timely payment of contributions, these generate fines that affect the institution financially, for which there are no monetary funds to cancel them, it is precisely at that moment that the amounts that are the object of this case study are generated: employer default and employer responsibility.